Sense making of the quality assurance framework and quality teaching in three private universities in Uganda - Bbaale, Benjamin (Kampala, 2015)
Unpublished dissertation ( M.A. ED. POL & PLAN) - Makerere Universit y, 2015.
Includes bibliographical references.
Keywords: Private universities and colleges -- Uganda; Lecturers and lecturing -- Uganda